Aktualisasi Nilai Historis & Teoritis dalam Pemberlakuan Hukum Islam di Indonesia - Azzahra, Fatimah; Mutawali, Muhammad; Syukri, Syukri (Tasyri' : Journal of Islamic Law, 2025)
Islamic law is a set of Islamic rules and norms sourced from the Quran and Hadith, coupled with the sources of Islamic law in the form of Ijma' and Qiyas, and the sources of ijtihad that are still debated by scholars in their use in the form of Istihsan, Istislah, Istishab, Maslahah Mursalah, 'Urf, Sar'u Man Qablana, and so on. The history of the birth of Islamic law began with the appointment of Muhammad as the last Prophet and Apostle, and was sent to this earth as the recipient of divine revelation that must be disseminated to his people until the Day of Resurrection arrives. The revelations collected into the Qur'an contain all the rules that are allowed and not allowed to be done as believers. The Quran and Hadith are final even though they can still be interpreted according to the development of the times until now. With the spread of Islam to all corners of the world, Islamic law is also included in it. Islam reached Indonesia at a time when the Hindu-Buddhist kingdoms still ruled Indonesia. Islam was brought peacefully by Arab and Indian traders so that it could be well received by the indigenous people at that time. The implementation of Islamic law in Indonesia has occurred since the birth of Islamic kingdoms until the current modern Indonesian era. This is evidenced by the use of Islamic law as the basis / source of various rules in Indonesia